MANAGEMENT OF LOCAL ENTREPRENEURIAL ECOSYSTEMS FOR REGIONAL DEVELOPMENT - ZAHORIANSKA, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article focuses on the pressing issue of improving the management of local entrepreneurial ecosystems (LEEs) in the context of wartime and post-war recovery, which is particularly relevant for Ukraine. It is dedicated to the study and systematization of contemporary approaches to network governance and effective interaction among key stakeholders: municipalities, the academic sector, business, and donor organizations. The primary focus is on supporting and accelerating the development of innovative startups, which are a driving force for economic growth. The paper argues that universities and other research centers play a critically important role not only as a source of skilled human capital but also as generators of applied innovations. They act as a central hub where the synergy of scientific knowledge and practical experience occurs, forming the foundation for creating competitive business solutions. Using the example of Kremenchuk, the article provides a detailed analysis of a successful case involving the integration of digital services, phased financial support, and university initiatives. This comprehensive approach has significantly shortened the path from idea generation to successful commercialization, which in turn has increased the resilience and adaptability of the local economy amidst extraordinary challenges. This case study serves as a model for other communities seeking to activate their entrepreneurial potential. The article proposes a set of practical tools that create a holistic and continuous ecosystem of support for startup projects. These tools are visualized through a management model for the interaction of LEE participants throughout the entire startup cycle. Key elements of this model include the creation of a Unified Contact Center for coordination, the development of a flexible “financing pipeline” (from grants to venture capital), the launch of a university academic entrepreneurship club for mentorship and skill development, the implementation of a public performance dashboard to ensure transparency and progress evaluation, and the establishment of guarantee mechanisms for investors to mitigate their risks. The findings of this research have significant practical value and can be utilized by other territorial communities in Ukraine for the effective development of their own LEEs. This is crucial for accelerating the post war recovery of the regional economy and ensuring its long-term competitiveness.
Keywords: local entrepreneurial ecosystem; start-up management; universities; financial support; regional development